Analysis The Student Perception of Application Clinical Skills Online Learning in The Pandemic Time Covid-19 - Anik Puji Rahayu; Sulistiyawati Sulistiyawati; Cicih Bhakti Purnamasari; Endang Sawitri; Ika Fikriah (Jurnal Keperawatan Padjadjaran, 2021)
Background: Government policies that apply social distancing, work from home, and learn from home to prevent the spread of the Covid-19 corona virus have an impact on learning methods. Clinical learning methods in pre-pandemic health education are carried out in campus laboratories and direct clinical services to patients. Thus, in this condition, the provision cannot be implemented. Purpose: For this reason, it is necessary to modify the learning method from offline to online to meet the continuity of the student learning process. Methods: In the first stage, the clinical skills online learning method using online videos is supported by lecturers’ explanations in a 120-minute meeting. In the second stage, students are given the task of making videos of procedural skills that have been taught in 170 minutes, with a video duration of 10-15 minutes. At the next meeting, a review or response is carried out with students on the standard operating procedure and the theory that underlies it. The design in this study is a descriptive analysis with 511 respondents from the medical education study program and the nursing diploma 3 study program at the Faculty of Medicine, Mulawarman University. The research used was 44 items of statement questionnaire that had been tested for validity and reliability, and questionnaire items were sent to respondents via Google Forms. Results: From the results of this study, there is a significant relationship between the perceptions of students who apply clinical skills online learning seen from the effectiveness of learning in the Covid-19 pandemic era with p-value = 0.000, with a very strong relationship with the Spearman value rho of 0.791 in a positive direction. Conclusion: Thus, it can be concluded that the application of online clinical skills learning during the Covid-19 pandemic was effective. As a suggestion, clinical learning methods with various blended learning or hybrid learning methods should be modified.